FROM CALLIGRAPHY TO CONCEPTUAL: THE TRANSFORMATION OF ISLAMIC IDEAS IN MODERN MALAYSIAN ART PRACTICE IN THE 1970S - Shahir, Safrizal (PEOPLE: International Journal of Social Sciences, 2025)
This paper examines the transformation of Islamic ideas in modern art practice in Malaysia, focusing on the 1970s, a period marked by a shift from calligraphic visualization to conceptual expression. The development of modern Malaysian art is unique, emerging from the ideological convergence influenced by Islam as a way of life (ad-din) and the injection of Western modern values during the British colonial era. This context has given rise to dilemmas and questions regarding the identity of Islamic and modern art in Malaysia. This review identifies two main approaches to integrating Islamic elements into local modern art. Firstly, an approach where Western forms absorb Islamic elements, commonly adopted by artists formally trained in Western fine arts, who imbue their works with Islamic images, motifs, or techniques such as Jawi script. Syed Ahmad Jamal and Husin Hourmain exemplify this by leveraging the plasticity of Jawi script for modern expression. Secondly, a less common approach, where Islamic visual forms absorb Western elements, as seen in the work of Haji Omar Basaree, a trained calligrapher who applies modern styles in traditional khat art. The 1970s witnessed a growing awareness among Malay artists to revisit their cultural and traditional roots. This spurred a deeper exploration of Islamic ideas, moving beyond the decorative use of Jawi script to a profound engagement with Islamic metaphysics and cosmology. Artists such as Ponirin Amin and Zakaria Awang demonstrated a propensity for conceptual works that convey contemplation and personal monologues with Islam. This transformation signifies an evolution in the understanding and representation of Islam within Malaysian modern visual art, progressing from superficial visual elements to more sophisticated and profound interpretations, reflecting an ideological shift from modern to contemporary.